Traveling wave solutions of the nonlinear Drinfel’d–Sokolov–Wilson equation and modified Benjamin–Bona–Mahony equations - Kamruzzaman Khan; M. Ali Akbar; Md. Nur Alam (Journal of the Egyptian Mathematical Society, 2013)
In this paper, the modified simple equation (MSE) method is implemented to find the exact solutions for the nonlinear Drinfel’d–Sokolov–Wilson (DSW) equation and the modified Benjamin–Bona–Mahony (mBBM) equations. The efficiency of this method for constructing these exact solutions has been demonstrated. It is shown that the MSE method is direct, effective and can be used for many other nonlinear evolution equations (NLEEs) in mathematical physics. Moreover, this technique reduces the large volume of calculations.